Prevalência de dispepsia e fatores sociodemográficos Prevalence of dyspepsia and associated sociodemographic factors - Sandro Schreiber de Oliveira; Iná da Silva dos Santos; José Francisco Pereira da Silva; Eduardo Coelho Machado (Universidade de São Paulo, 2006)
OBJETIVO: Medir a prevalência e distribuição de dispepsia e dispepsia freqüente por subtipos na população com 20 anos ou mais segundo características socioeconômicas e demográficas. MÉTODOS: Estudo transversal, de base populacional, com 3.934 indivíduos moradores na cidade de Pelotas (RS), entrevistados em seus domicílios, de outubro de 1999 a janeiro de 2000. Dispepsia foi definida como dor ou desconforto no andar superior do abdome e/ou náuseas no ano anterior à entrevista (conforme critérios Roma I e II). Dispepsia freqüente incluiu o registro de dispepsia mais de seis vezes e/ou náuseas, uma vez por mês ou mais. Esses desfechos foram analisados por idade, sexo, cor da pele, escolaridade, renda e estado civil. Os dados foram analisados por meio do teste qui-quadrado de Pearson de associação para variáveis categóricas e teste de tendência linear, quando aplicável. RESULTADOS: A prevalência de dispepsia foi de 44,4% e de dispepsia freqüente, 27,4%. A prevalência de dispepsia tipo refluxo, úlcera, dismotilidade e não especificada foi, respectivamente, 19,4%, 6,3%, 13,9% e 16,6%; para dispepsia freqüente foram 14,7%, 4,9%, 11,2% e 6,8%, respectivamente. As mulheres apresentaram cerca de 50% mais dispepsia freqüente. Indivíduos mais jovens e de menor renda apresentaram maiores prevalências de dispepsia e dispepsia freqüente. Análise de acordo com critérios de Roma II mostrou prevalências de 15,9% e 7,5% para dispepsia e dispepsia freqüente, respectivamente. CONCLUSÕES: A dispepsia constitui um problema prevalente na população estudada. A maioria dos indivíduos apresentaram mais de um subtipo de dispepsia. OBJECTIVE: To assess prevalence of dyspepsia and distribution of dyspepsia and frequent dyspepsia in subgroups of adults (20 years and older) according to their demographic and socioeconomic characteristics. METHODS: A cross-sectional population-based study was carried out comprising 3,934 subjects living in Pelotas, Southern Brazil, from October 1999 to January 2000. Data was collected through household interviews. Dyspepsia was defined as epigastric pain or disconfort associated or not with nausea in the previous year, according to Rome I and Rome II criteria. Frequent dyspepsia was defined as more than six dyspepsia episodes in the previous year and/or nausea, at least once a month. These outcomes were analyzed according to age, gender, skin color, educational level, per capita income and marital status. Data analysis was carried out through Pearson Chi-square test for categorical variables and linear trend test, when applicable. RESULTS: The prevalence of dyspepsia was 44.4% and frequent dyspepsia, 27.4%. The prevalences of reflux-like, ulcer-like, dysmotility-like and unspecific dyspepsia subtypes were 19.4%, 6.3%, 13.9%, and 16.6%, respectively. The prevalences of these subtypes of frequent dyspepsia were 14.7%, 4.9%, 11.2% and 6.8%, respectively. Prevalences among women were 50% higher. Low-income young people seemed to be more affected by dyspeptic symptoms. The analysis according to Rome II criteria showed prevalences of 15.9% and 7.5% for dyspepsia and frequent dyspepsia, respectively. CONCLUSIONS: Dyspepsia and frequent dyspepsia were prevalent problems in the studied population. Most people could be classified in more than one subgroup of dyspepsia.